2012
DOI: 10.1681/asn.2011040367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Integrin α2β1 Ameliorates Glomerular Injury

Abstract: Mesangial cells and podocytes express integrins a1b1 and a2b1, which are the two major collagen receptors that regulate multiple cellular functions, including extracellular matrix homeostasis. Integrin a1b1 protects from glomerular injury by negatively regulating collagen production, but the role of integrin a2b1 in renal injury is unclear. Here, we subjected wild-type and integrin a2-null mice to injury with adriamycin or partial renal ablation. In both of these models, integrin a2-null mice developed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
1
47
0
1
Order By: Relevance
“…45 Recently, Inta2/b1 was shown to exert a deleterious effect in glomerular injury by upregulating collagen production. 46 Our findings in a model of ADPKD expand these observations to the collecting ducts, thus strengthening the role of Intb1 in the renal fibrotic process. 47 The reciprocal control of integrins on matrix deposition 48 and ECM on integrin activation makes it difficult to determine whether the upregulation of integrin or ECM comes first.…”
Section: Discussionsupporting
confidence: 79%
“…45 Recently, Inta2/b1 was shown to exert a deleterious effect in glomerular injury by upregulating collagen production. 46 Our findings in a model of ADPKD expand these observations to the collecting ducts, thus strengthening the role of Intb1 in the renal fibrotic process. 47 The reciprocal control of integrins on matrix deposition 48 and ECM on integrin activation makes it difficult to determine whether the upregulation of integrin or ECM comes first.…”
Section: Discussionsupporting
confidence: 79%
“…In a more recent study, reduced pathological neovascularization in integrin α2 −/− mice was observed in a model for retinopathy (Madamanchi et al, 2014a). The absence of α2 is known to delay fibrosis and glomerular damage in experimental kidney disease models, including the Alport syndrome mouse model (Borza et al, 2012;Rubel et al, 2014). Moreover, another more recent study has demonstrated a role for α2β1 in inflammation during rheumatoid arthritis, with reduced disease severity in integrin α2 −/− mice (El Azreq et al, 2015).…”
Section: Integrin α2β1mentioning
confidence: 95%
“…Interactions between cells with the surrounding extracellular matrix have emerged as a key factor involved in the initiation and progression to fibrosis (1). Integrins ␣1␤1 and ␣2␤1 are the key extracellular matrix receptors that regulate collagen turnover in many organs, including skin (2, 3) and kidneys (4,5). These integrins bind to collagens via their extracellular domains, resulting in the activation of intracellular signaling pathways via their cytoplasmic tails.…”
mentioning
confidence: 99%